2017
DOI: 10.1155/2017/2362056
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Surface Morphology and Dispersion Media on the Properties of PEDOT:PSS/n-Si Hybrid Solar Cell Containing Functionalized Graphene

Abstract: We present the results on the effect of surface morphology and dispersion media on the properties of PEDOT:PSS/n-Si hybrid solar cell containing functionalized graphene (Gr). The hybrid solar cells based on SiNWs showed higher power conversion efficiency (PCE) compared to the planar based cells due to suppressing the carrier recombination and improving carrier transport efficiency. The PCE of hybrid solar cells could be improved by adding Gr into PEDOT:PSS. Different solvents including deionized (DI) water, et… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 43 publications
0
7
0
2
Order By: Relevance
“…In 2017, Pham et al systematically studied the impact of different solvents (deionized (DI) water, EG,a nd IPA) on the performances of HSCs containing carboxyl (COOH)-functionalized Gr.T he highest PCE of 7.33 %was achieved using Gr dispersed in EG,w ith av alue 13 %a nd 16 %higher than that from Gr dispersed in IPAa nd DI water, respectively. [32] Thea ddition of reduced graphene oxide (rGO) flakes to PEDOT:PSS was verified to produce an antireflection coating for reducing reflectance.Meanwhile,the interaction between the rGO flakes and PEDOTdecreased the sheet resistance of the PEDOT:PSS layer, causing an enhanced power output of the HSC with ahigher J SC of 31.94 mA cm À2 . [26] In 2018, Li et al reported the application of mixed Ag and Au nanoparticles (NPs) in HSCs.Aprolonged charge carrier lifetime with suppressed charge recombination was detected in the dual NP-incorporated system.…”
Section: Addition Of Nanomaterialsmentioning
confidence: 99%
“…In 2017, Pham et al systematically studied the impact of different solvents (deionized (DI) water, EG,a nd IPA) on the performances of HSCs containing carboxyl (COOH)-functionalized Gr.T he highest PCE of 7.33 %was achieved using Gr dispersed in EG,w ith av alue 13 %a nd 16 %higher than that from Gr dispersed in IPAa nd DI water, respectively. [32] Thea ddition of reduced graphene oxide (rGO) flakes to PEDOT:PSS was verified to produce an antireflection coating for reducing reflectance.Meanwhile,the interaction between the rGO flakes and PEDOTdecreased the sheet resistance of the PEDOT:PSS layer, causing an enhanced power output of the HSC with ahigher J SC of 31.94 mA cm À2 . [26] In 2018, Li et al reported the application of mixed Ag and Au nanoparticles (NPs) in HSCs.Aprolonged charge carrier lifetime with suppressed charge recombination was detected in the dual NP-incorporated system.…”
Section: Addition Of Nanomaterialsmentioning
confidence: 99%
“…Mit Gr in EG wurde der beste PCE von 7.33 % erreicht, und der Vorsprung gegenüber den entsprechenden Werten für Gr in IPA und DI‐Wasser betrug 13 % bzw. 16 % [32] . Ein PEDOT:PSS‐Zusatz aus flockenförmigem reduziertem Graphenoxid (rGO) wirkte als Antireflexionsschicht und reduzierte den Reflexionsgrad.…”
Section: Modifizierung Von Pedot:pssunclassified
“…MacEtch is one of the anisotropic methods for obtaining Si nanostructures of different morphologies, in particular porous Si [1][2][3][4], nanowires, and complex nanostructures [5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…is is primarily due to the value of the standard electrode potential for the metal (E 0 N n+ /N ). erefore, metals which are characterized by high values of this parameter, such as noble metals (Au, Pt, Ag, and Pd), are used for MacEtch [8,14,[19][20][21]. Noble metals are also characterized by high chemical and electrochemical resistance at the nanoscale level.…”
Section: Introductionmentioning
confidence: 99%